Analytical models of IP traffic on UMTS mobile networks - Landman, Jesse (Department of Computer Science, 2024)
Mobile communications networks are becoming ubiquitous worldwide. Such networks have achieved high rates of success in the area of connected voice traffic. An example of such a network is the Global System Mobile (GSM) cellular network. It is apparent that these networks are also able to offer packet-switched services such as IP for Internet and email browsing. The GPRS extension to GSM networks is a working example of this. However, it is necessary to completely overhaul such Second Generation (2G) networks in order to provide high data rates for packet services. In this dissertation we investigated the performance of IP traffic over UMTS networks. UMTS is a Third Generation (3G) replacement for GSM technologies and consists of a land-based Core Network and a UMTS Radio Access Network (UTRAN). UMTS networks utilise Code Division Multiple Access (CDMA) technologies to multiplex the radio resources available to the network. CDMA allows for all users of the network to transmit simultaneously, reducing the need to multiplex using time (TDMA) or frequency (FDMA). CDMA channels do however experience multipath fading as well as multiple access interference. Our investigation involved deriving two analytical models, one that would model the queueing and processing on the CN, and one that would model the transmission errors on the UTRAN.